Pengaruh Inovasi Produk, Promosi Digital Dan Kepuasan Pelanggan Terhadap Keberlanjutan Usaha Pembelian : Studi Kasus UMK Gethuk Take Tawangmangu - Alfrin Sefanya Dillak; Dokman Marulitua Situmorang (Jurnal Minfo Polgan, 2026)
This Study Aims To Analyze The Influence Of Product Innovation, Digital Promotion, And Customer Satisfaction On Business Sustainability At The Gethuk Take Tawangmangu Msme. This Study Used A Quantitative Approach With Data Collection Techniques Through The Distribution Of Questionnaires To Respondents. The Population In This Study Were Consumers Of The Gethuk Take Tawangmangu Msme, With A Sample Of 96 Respondents Determined Using A Specific Sampling Technique. Data Analysis Was Conducted Using Validity Tests, Reliability Tests, Classical Assumption Tests, Multiple Linear Regression Analysis, T-Tests, F-Tests, And Coefficient Of Determination (R²) Tests Processed Using Spss Software. The Results Showed That Product Innovation Had A Positive And Significant Effect On Business Sustainability. Digital Promotion Also Showed A Positive And Significant Effect On Business Sustainability. Furthermore, Customer Satisfaction Was Proven To Have A Positive And Significant Effect On Business Sustainability. The Results Of Simultaneous Testing Showed That Product Innovation, Digital Promotion, And Customer Satisfaction Together Had A Significant Effect On Business Sustainability. The Coefficient Of Determination (R²) Of 0.535 Indicates That 53.5% Of The Variation In Business Sustainability Can Be Explained By These Three Variables, While The Remaining 46.5% Is Influenced By Factors Outside The Research Model. The Findings Of This Study Indicate That Increasing Product Innovation, Optimizing Digital Promotions, And Maintaining Customer Satisfaction Are Important Factors In Supporting Business Sustainability At The Gethuk Take Tawangmangu Msme.